Α-MoO3 nanostructure on carbon cloth substrate for dopamine detection. (10th April 2019) - Murugesan, D; Moulaee, K; Neri, G; Ponpandian, N; Viswanathan, C
Abstract: Orthorhombic molybdenum oxide ( α -MoO3 ) nanostructures were deposited on the surface of carbon cloth (CC) as a flexible and high conductive scaffold by reactive RF magnetron sputtering technique. Structure and morphology of the as prepared molybdenum coated carbon cloth (MoO3 CC) were thoroughly characterized with field emission scanning electron microscopy, x-ray diffraction, energy dispersive x-ray and Raman spectroscopy. Benefiting from high surface area and superior conductivity of CC as well as electrocatalytic activity of α -MoO3 nanostructures, an electrochemical sensor was fabricated. The electrochemical behavior of this new sensor toward determination of dopamine was studied in detail by cyclic voltammetry, amperometry (AM) and square wave voltammetry (SWV). Results reported here reveal that using SWV not only enhances the sensitivity of sensors to dopamine by more than 14 times compared to AM, but also offers higher linear dynamic range (1–700 μ M compared to 5–550 μ M). Limit of detection, for signal to noise ratio 3, was calculated to be 0.48 μ M. Applicability of the proposed sensor for measurement of dopamine in real samples, like urine and pharmaceutical formulation, was also evaluated that concluded to satisfactory results.